2017
DOI: 10.1186/s12931-017-0660-4
|View full text |Cite
|
Sign up to set email alerts
|

Vildagliptin ameliorates pulmonary fibrosis in lipopolysaccharide-induced lung injury by inhibiting endothelial-to-mesenchymal transition

Abstract: BackgroundPulmonary fibrosis is a late manifestation of acute respiratory distress syndrome (ARDS). Sepsis is a major cause of ARDS, and its pathogenesis includes endotoxin-induced vascular injury. Recently, endothelial-to-mesenchymal transition (EndMT) was shown to play an important role in pulmonary fibrosis. On the other hand, dipeptidyl peptidase (DPP)-4 was reported to improve vascular dysfunction in an experimental sepsis model, although whether DPP-4 affects EndMT and fibrosis initiation during lipopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 45 publications
6
73
0
Order By: Relevance
“…Since FBs also constitute the center of fibrotic disease etiology in other organs, this finding might have important implications beyond the skin. 1,60 In animal studies, DPP4 + FBs have been shown to be involved in fibrotic pathologies of several other organs, and inhibition of DPP4 activity by gliptins attenuated fibrotic processes in the lung, 61 heart, 62,63 kidney, 64 and liver. 65 Therefore, our transcriptome analysis of DPP4 + FBs in the human skin might represent an important step toward the development of novel anti-fibrotic therapeutic approaches, specifically targeting the DPP4 + FB subset.…”
Section: Discussionmentioning
confidence: 99%
“…Since FBs also constitute the center of fibrotic disease etiology in other organs, this finding might have important implications beyond the skin. 1,60 In animal studies, DPP4 + FBs have been shown to be involved in fibrotic pathologies of several other organs, and inhibition of DPP4 activity by gliptins attenuated fibrotic processes in the lung, 61 heart, 62,63 kidney, 64 and liver. 65 Therefore, our transcriptome analysis of DPP4 + FBs in the human skin might represent an important step toward the development of novel anti-fibrotic therapeutic approaches, specifically targeting the DPP4 + FB subset.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published one-year randomized controlled clinical trial indicated that vildagliptin administration mitigates the reduction in the number of endothelial progenitor cells in type 2 diabetes patients [28]. Another recent study showed that vildagliptin treatment protects endothelial cells from loss of identity towards transformation into other cell types and improves pulmonary fibrosis in mice [29]. All these evidences demonstrate that vildagliptin possesses an array of vascular protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…They found (1) a CD26 mediated costimulation of T-cells combined with production of the proinflammatory interleukin-2 (IL-2) [59], (2) a CD26 mediated co-stimulation of CD8 + T cells, which exert cytotoxic effects predominantly via TNF-α [18], (3) a DPP4 dependent cleavage of the chemokine substrate LD78ß into a very efficient monocyte attractant, enhancing lymphocyte and monocyte chemotactic activity [60], and (4) a CD26/DPP4inhibitor dependent increase of the anti-inflammatory peptide VIP (Vasointestinal peptide) in rats [61], diminishing inflammatory response [15,21]. Furthermore, using different CD26/DPP4 inhibitors signs of inflammation were reduced in different lung disease models [22,62,63]. Not at all, our group found a reduced inflammation in CD26/ DPP4 − rats [24].…”
Section: Cd26/dpp4 Dependent Differencesmentioning
confidence: 99%